2022
DOI: 10.1021/acsomega.2c03053
|View full text |Cite|
|
Sign up to set email alerts
|

Therapeutic Potential of Standardized Extract of Melilotus indicus (L.) All. and Its Phytochemicals against Skin Cancer in Animal Model: In Vitro, In Vivo, and In Silico Studies

Abstract: Melilotus indicus (L.) All. is known to have anti-inflammatory and anticancer properties. The present study explored the in vivo skin carcinogenesis attenuating potential of ethanolic extract of M. indicus (L.) All. (Miet) in a 7,12-dimethylbenz[ a ]anthracene (DMBA)-induced skin cancer model. The ethanolic extract of the plant was prepared by a maceration method. HPLC analysis indicated the presence of quercetin in abundance and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…5 People are interested in herbal therapies due to aforementioned negative effects of conventional therapies. [11][12][13] Pharmacological and therapeutic efficiency of herbal drugs is attributable due to the existence of many phytoconstituents, which may be utilized to treat a variety of ailments. [14][15][16] Herbal therapies for PCOS have been reported to be quite effective in reducing hyperandrogenism, obesity and improving ovulation and insulin sensitivity with no major side effects.…”
Section: Introductionmentioning
confidence: 99%
“…5 People are interested in herbal therapies due to aforementioned negative effects of conventional therapies. [11][12][13] Pharmacological and therapeutic efficiency of herbal drugs is attributable due to the existence of many phytoconstituents, which may be utilized to treat a variety of ailments. [14][15][16] Herbal therapies for PCOS have been reported to be quite effective in reducing hyperandrogenism, obesity and improving ovulation and insulin sensitivity with no major side effects.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, we have seen health care systems that recognized the importance of food-based, alternative, and complimentary medicines. This incline is might be due to better awareness of toxicity profile of all the above allopathic regimens or due to higher cost [ 14 , 15 ]. Phytochemicals present in herbal remedies and medicinal plant are source of therapeutic effectiveness against the ailment such as PCOS [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another phytochemical study of Melilotus indicus, belonging to the same plant genus, revealed the presence of compounds nearly identical to those obtained in our study. These compounds include quercetin, gallic acid, caffeic acid, vanillic acid, chlorogenic acid, syringic acid, p -coumaric acid, and m -coumaric acid . Furthermore, additional studies have demonstrated the richness of M.…”
Section: Results and Discussionmentioning
confidence: 99%